2015
DOI: 10.5688/ajpe79572
|View full text |Cite
|
Sign up to set email alerts
|

Training and Support of Sessional Staff to Improve Quality of Teaching and Learning at Universities

Abstract: Sessional staff is increasingly involved in teaching at universities, playing a pivotal role in bridging the gap between theory and practice for students, especially in the health professions, including pharmacy. Although sessional staff numbers have increased substantially in recent years, limited attention has been paid to the quality of teaching and learning provided by this group. This review will discuss the training and support of sessional staff, with a focus on Australian universities, including the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…6 Moreover, the type and depth of training differs and no accurate measurable rule of its judgment. 16 The higher response of female staff than males was also, reported previously by Ramírez-Correa. 17 They concluded that significant differences between males and females when adopting an e-learning platform training were documented in their study.…”
Section: Discussionsupporting
confidence: 76%
“…6 Moreover, the type and depth of training differs and no accurate measurable rule of its judgment. 16 The higher response of female staff than males was also, reported previously by Ramírez-Correa. 17 They concluded that significant differences between males and females when adopting an e-learning platform training were documented in their study.…”
Section: Discussionsupporting
confidence: 76%
“…The quality of teaching at tertiary level has never been more important to student outcomes and workforce contributions [ 4 ]. High quality teaching, according to Queensland University of Technology [ 5 ], should capture students into a learning partnership whereby personal and professional development is inspired, fostered, and ultimately practised as new graduates.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature on the evolution of staff and student development programmes in higher education focus on the need to improve the quality and effectiveness of teaching and learning in higher education (Scott, Yeld & Hendry, 2007). However, with widened access and an increase in student numbers, the pressure on academic staff to be involved in research and publication in the face of reduced funding has led to a need for additional academic support (Knott, Crane, Heslop, Glass, 2015). This was recognised by Boughey (2007: 3) who suggested that institutional development focus on "systemic and institutional efficiency" to support teaching and learning.…”
Section: Dr Xena Michelle Cupidomentioning
confidence: 99%